Black market and official exchange rates: long-run equilibrium and short-run dynamics - Guglielmo Maria Caporale; Mario Cerrato (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper presents further empirical evidence on the relationship between black market and official exchange rates in six emerging economies (Iran, India, Indonesia, Korea, Pakistan, and Thailand). First, it applies both time series techniques and heterogeneous panel methods to test for the existence of a long-run relationship between these two types of exchange rates. Second, it tests formally the validity of the proportionality restriction implying a constant black-market premium. Third, it also analyses the short-run dynamic responses of both markets to shocks. Finally, it tries to shed some light on the determinants of the market premium. Evidence of slow reversion to the long-run equilibrium is found. Further, it appears that capital controls and expected currency devaluation are the two main factors affecting the size of the premium and determining the breakdown in the proportionality relationship.
Keywords: C23; F31; 330; Wechselkurs; Schwarzmarkt; Zeitreihenanalyse; Iran; Indien; Indonesien; Südkorea; Pakistan; Thailand